The strategy for the development of electronic publishing in small markets (Libellarium: journal for research in the field of information and related sciences, 2014)
This paper analyses technological trends which affect the business models in the publishing industry and create innovative publishing products which reflect the reader's needs in the digital environment. Although technology already offers many possibilities, the way it is used is both a technical and a market-related issue. The migration to the digital environment has stimulated major changes in publishing and other media industries. Publishing sectors such as scientific publications quickly accept the new technological opportunities. Free content and self-publishing models shake the publishing industry and change the publisher's traditional position in the book publishing chain. Advanced software solutions offer authors easy access to virtual ‘shelves’, allowing publishers a simpler, quicker production and distribution. Changes carry many challenges and threats since the technology is still at an early stage of implementation. This paper presents new trends and predictions, and their potential impact on publishing, with a special focus on small linguistic distribution markets such as the Croatian book market.
Keywords: electronic publishing; self-publishing; free content; strategy; Croatia